Hypervolemia and physiology changes in triplet pregnancy in a mother with permanent pacemakers due to bradicardia resulting from sinus node dysfunction due to AV block with secondary infertility for 19 years - Sungkar, Ali; Maulina, Fita; Dilmy, M Adya F (Majalah Obstetri & Ginekologi, 2020)
The well-known hypervolemia associated with normal pregnancy averages 40 to 45 percent above blood volume in non-pregnant women after 32 to 34 weeks. The case was on Mrs. FN, 40 years old, a patient reffered due to sinus bradycardia before the insertion of permanent pacemaker. After 6 month-use of the permanent pacemaker, she became pregnant with triplet pregnancy. This case report evaluated the patient’s condition from her hypervolemic condition to her cardiac function.